Charting the course: our 2023 strategic action plan / Muhammad Aiman Abdul Halim - Abdul Halim, Muhammad Aiman (Academy of Language Studies, 2023)
Recently, the APB UiTMCPP staff members were enlisted to assist with our department's strategic action planning for 2023. The staff members were grouped into four teams and conducted brainstorming sessions to propose strategic action plans. With each member possessing unique skills and expertise, the groups collectively evaluated the department's latest performance indicators and discussed potential contributions towards their attainment. The discussions were fruitful, and each group had done a great job in completing their planning task. They have identified the critical areas of focus and outlined the necessary steps to achieve the department's goals. The staff members have also brainstormed ideas on how to overcome some challenges that may arise during the implementation of the plans. As the Strategic Planning Committee for APB UiTMCPP, I have consolidated the strategic action plans generated by each group and presented them in an infographic. The activities are categorized according to their potential contributions to the main performance indicators, allowing for a clear and organized overview of our planned initiatives